Raising rabbits and ducks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Tshala Mwengo, of Musokatanda Agriculture and Family Health Project in Katanga Province, Democratic Republic of Congo, writes to share an innovation with readers of Spore. 'We specialise in integrated small animals, crop, fish culture and animal...